Inhibition of Corn Oil Peroxidation by Extracts from Defatted Seeds of Camellia oleifera Abel - Haiming Chen; Fei Song; Weijun Chen; Wenxue Chen (Journal of Food Quality)
The defatted seed of Camellia oleifera Abel is an underexploited byproduct. In the present study, 3 solvents (isopropanol, hexane, and diethyl ether) were used to extract active compounds from defatted seeds of Camellia oleifera Abel. The qualitative and quantitative characterization of the main phenolic compounds were performed using the HPLC-DAD. In addition, the antioxidant efficacy of defatted seed extracts in the stabilization of the corn oil was estimated by monitoring its primary and secondary oxidation products. The results showed that isopropanolic extract (IE) exhibited the highest yield of total phenolic compounds (9.23±0.33 mg/g) compared with other solvents. The predominant phenolic compounds identified by HPLC-DAD in defatted seed extracts were epicatechin, naringenin, and catechin. In addition, IE exhibited the best inhibition effect on both primary and secondary oxidation products. The results reveal that IE of defatted seed of Camellia oleifera Abel is a useful antioxidant for the stabilization of corn oil.